2023
DOI: 10.3390/cells12030355
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Changes in the Corpus Callosum in Systemic Lupus Erythematous

Abstract: Central nervous system (CNS) involvement in childhood-onset systemic lupus erythematosus (cSLE) occurs in more than 50% of patients. Structural magnetic resonance imaging (MRI) has identified global cerebral atrophy, as well as the involvement of the corpus callosum and hippocampus, which is associated with cognitive impairment. In this cross-sectional study we included 71 cSLE (mean age 24.7 years (SD 4.6) patients and a disease duration of 11.8 years (SD 4.8) and two control groups: (1) 49 adult-onset SLE (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Within SLE subgroups, one study reported large affected areas in SLE patients with and without memory deficits vs controls (lower FA and higher MD/RD) 30 . Another study evaluated patients with cSLE vs aSLE and reported lower FA and higher diffusivities in the corpus callosum in the former relative to the latter subgroup 26 , while no diffusion differences were observed between NPSLE and non-NPSLE patients in two manuscripts 19,24 . No changes in diffusion metrics in patients with SLE after the follow-up period were observed in the DTI publication with longitudinal data 25 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Within SLE subgroups, one study reported large affected areas in SLE patients with and without memory deficits vs controls (lower FA and higher MD/RD) 30 . Another study evaluated patients with cSLE vs aSLE and reported lower FA and higher diffusivities in the corpus callosum in the former relative to the latter subgroup 26 , while no diffusion differences were observed between NPSLE and non-NPSLE patients in two manuscripts 19,24 . No changes in diffusion metrics in patients with SLE after the follow-up period were observed in the DTI publication with longitudinal data 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Three manuscripts reported information regarding race/ethnicity, and in two of them over half of the patients were African-Americans (6/11 – 55%, and 14/20 – 70% of their respective cohorts 25,27 ). Cohort ages ranged 14.7-48.9 years on average with a pooled mean of 35.5 years; 16/18 studies examined adult patients with SLE, 2/18 included patients with cSLE 27,28 , and one compared patients with aSLE versus cSLE 26 . Healthy controls with age and sex distributions comparable to their respective SLE cohorts were utilized for group comparisons in 16/18 studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations